Clinical potential and mechanistic insights of mulberry (Morus alba L.) leaves in managing type 2 diabetes mellitus: Focusing on gut microbiota, inflammation, and metabolism. (24th April 2023) - Tang, Cheng; Bao, Tingting; Zhang, Qiqi; Qi, Hongyu; Huang, Yishan; Zhang, Boxun; Zhao, Linhua; Tong, Xiaolin
Abstract: Ethnopharmacological relevance: Natural herbs are gradually gaining recognition for their efficacy and safety in preventing diabetes and improving quality of life. Morus alba L. is a plant widely grown in Asia and is a traditional Chinese herb with a long history of use. Furthermore, several parts of Morus alba L. have been found to have significant health benefits. In particular, mulberry ( Morus alba L.) leaves (ML) have been shown in human and animal studies to be promising hypoglycemic agents that can reduce or prevent glucolipid metabolism disorders caused by imbalances in the gut microbiota, inflammation, and oxidative stress and have demonstrated significant improvements in glucose metabolism–related markers, effectively lowering blood glucose, and reducing hyperglycemia–induced target organ damage. Aim of the study: This review briefly summarizes the methods for obtaining ML's bioactive components, elaborates on the clinical potential of the relevant components in managing type 2 diabetes mellitus (T2DM), and focuses on the therapeutic mechanisms of gut microbiota, inflammation, oxidative stress, and metabolism, to provide more inspiration and directions for future research in the field of traditional natural plants for the management of T2DM and its complications. Materials and methods: Research on ML and its bioactive components was mainly performed using electronic databases, including PubMed, Google Scholar, and ScienceNet, to ensure the review's quality. In addition, master's and doctoral theses and ancient documents were consulted. Results: In clinical studies, we found that ML could effectively reduce blood glucose, glycated hemoglobin, and homeostasis model assessment of insulin resistance in T2DM patients. Furthermore, many in vitro and in vivo experiments have found that ML is involved in various pathways that regulate glucolipid metabolism and resist diabetes while alleviating liver and kidney damage. Conclusions: As a potential natural anti–diabetic phytomedicine, an in–depth study of ML can provide new ideas and valuable references for applying traditional Chinese medicine to treat T2DM. While continuously exploring its clinical efficacy and therapeutic mechanism, the extraction method should be optimized to improve the efficacy of the bioactive components. in addition, further research on the dose–response relationship of drugs to determine the effective dose range is required. Graphical abstract: Image 1 Highlights: Mulberry leaves have great potential to treat type 2 diabetes mellitus. Mulberry leaves can effectively reduce blood glucose and glycated hemoglobin. Mulberry leaves can regulate gut microbiota, inflammation, and oxidation.